Agricultural Productive Service System Based on the Block Chain and Edge Computing. (30th November 2020) - Wang, Yuqing; Han, Xueping
Abstract : With the rapid development of the service sector in economic growth, productive service industry has become a growing field of people's attention. Agricultural productive services are a supporting point to promote the development of modern agriculture, and at the same time, they also point out the direction for promoting the transformation of the agricultural development mode, which has very important strategic significance. In order to analyze and improve the rural productive service system and solve the "three rural" issues, this article designs an agricultural productive service analysis framework from the perspective of farmers, statistics of the investment in agricultural productive services in a certain region from 2015 to 2019, the expenditure of agricultural productive services in agriculture, forestry, fishery, and animal husbandry, and per capita wage income and operating income of farmers in the area under agricultural productive services, and in the process of agricultural production, farmers need agricultural productive services from the perspective of the whole process, land preparation, seeding, pest control, fertilization, and harvesting risks. The data in this experiment are stored in a distributed manner through the block chain, and the data are stored in the corresponding part in the chronological order; the data are transmitted to the edge server of the experimental network in the way of point-to-point transmission, and then edge computing technology is used to calculate and analyze the data collected in the experiment. The final result shows that, in this region, the input of the main agricultural producer service industry is growing very fast, the scale of productive services is expanding, and more and more attention is paid to the producer services in the process of agricultural production, but the internal composition of agricultural producer services is unbalanced. With the continuous improvement of the scale of agricultural productive services, the per capita income of farmers and the per capita income of management are also increasing year by year. When the scale of agricultural productive services reaches 0.09 in 2019, the per capita wage income of farmers has reached 3900 yuan, and the per capita income of farmers has reached 3750 yuan. And in the perspective of various risks in agricultural production, the higher the risk coefficient, the stronger the risk preference of farmers and the higher the risk investment in agricultural production services.